MYCELIAL AMYLASE AND CELLULASE CHARACTERIZATION AS WELL AS BASIDIOMA PHYSICOCHEMICAL ANALYSIS OF LINGZHI MUSHROOM - Yati Sudaryati Soeka; Muhammad Ilyas (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2021)
Karakterisasi Amilase dan Selulase Miselial Serta Analisis Fisikokimia Basidioma Jamur Lingzhi (Ganoderma lucidum) Lingzi mushroom (Ganoderma lucidum) synthesizes enzymes which have anti-hyperglycemic and anti-diabetic activities. This preliminary study aims to characterize the amylase and cellulase activities of mycelial culture, and to analyze the physicochemical compounds in the basidioma of G. lucidum InaCC F11 and G. lucidum InaCC F106. The enzymes were characterized spectrophotometrically using DNS method, and the basidioma was subjected to proximate and high performance liquid chromatography (HPLC) analysis, as well as microstructural observation using scanning electron microscope. Results showed both strains demonstrated amylase activity, but not cellulase activity. The optimum activity of amylase in G. lucidum InaCC F11 mycelial cultures was achieved on the 3rd incubation day, at pH 5.5, 35 ºC temperature, and 1.5% substrate concentration, whereas that of G. lucidum InaCC F106 on the 7th incubation day, at pH 5, 40 ºC temperature, and 1.75% substrate concentration. Dried basidioma of G. lucidum InaCC F11 contained 93.72% carbohydrates, 3.06% protein, 0.85% fat, 0.768% crude fiber, 0.54% ash, and 1.83% moisture. In addition, HPLC detected the presence of phenols (0.036%), steroids (0.014 mg 100 mL-1), and active triterpenoid compounds. Jamur lingzi (Ganoderma lucidum) mensintesis enzim yang memiliki aktivitas anti-hiperglikemik dan anti-diabetes. Studi pendahuluan ini bertujuan mengkarakterisasi aktivitas amilase dan selulase kultur miselium, serta menganalisis senyawa fisikokimia pada basidioma G. lucidum InaCC F11 dan G. lucidum InaCC F106. Enzim dikarakterisasi secara spektrofotometri menggunakan metode DNS. Basidioma dianalisis secara proksimat, menggunakan kromatografi cair kinerja tinggi (KCKT), serta diamati mikrostrukturnya menggunakan mikroskop elektron. Hasil menunjukkan kedua strain tersebut memiliki aktivitas amilase, dan tidak ada aktivitas selulase. Aktivitas amilase optimum pada kultur miselium G. lucidum InaCC F11 dicapai pada inkubasi hari ke-3, pH 5,5, suhu 35 ºC, dan konsentrasi substrat 1,5%, sedangkan pada kultur miselium G. lucidum InaCC F106 dicapai pada inkubasi hari ke-7, pH 5, suhu 40 ºC, dan konsentrasi substrat 1,75%. Basidioma kering G. lucidum InaCC F11 mengandung karbohidrat 93,72%, protein 3,06%, lemak 0,85%, serat kasar 0,768%, abu 0,54%, dan kadar air 1,83%. Selain itu, KCKT mendeteksi adanya fenol (0,036%), steroid (0,014 mg 100 mL-1), dan senyawa triterpenoid aktif.